(untitled) (Journal of Philosophy, Culture and Political Science, 2023)
In this article authors describe classification of scientific knowledge within the philosophy of al-Farabi. There is an attempt of humanistic ideals of al-Farabi’s description. Authors describe that philosophy of al-Farabi, as theoretical science gives considerable knowledge of meaning of the life. Authors analyze that according to scientist, deep mastering of philosophical knowledge is impossible without constant and persevering work, without love to it. In the article al-Farabi was described as greatest thinker of the Arabian medieval East. This article will greatly contribute to the theoretical significance of Al-Farabi researchers and scientists who are determined to study Central Asia. That is, we would like to draw attention to the fact that the teachings of The Thinker are always relevant. In practical terms, it can be used in any future scientific works, textbooks, special courses on Al-Farabi and students ‘ programs. Aim of the article is to analyze new aspects of al-Farabi’s understanding a reason and the essence of happiness achievement. Also, together with above mentioned aspects, we set up the additional objectives in the article. To achieve abovementioned goal, we used several research methods: systematization, induction, literature review and deduction. During our investigation, we came to conclusion that, al-Farabi belong- ing to antique, cultural epoch, has become the brightest representative of magnificent and inimitably fine Arabic-language Muslim civilization. In his works we found many significant ideas about: instinctive experience, morality, knowledge and beliefs, sciences and religions. Key words: Pantheism, achievement of happiness, scientific value, omniscience, dogmatic divinity, classification of scientific knowledge.